Expression and regulation of 42Sp50 in spotted scat (Scatophagus argus) - Zhi, Fei; Jiang, Dong-Neng; Mustapha, Umar Farouk; Li, Shao-Xiang; Shi, Hong-Juan; Li, Guang-Li; Zhu, Chun-Hua (Frontiers in Genetics, 2022)
42Sp50 is an isoform of the eukaryotic translation elongation factor 1 A (eEF1A) and is vital for fish ovarian development. Spotted scat (Scatophagus argus) is a popular marine cultured fish species in Southern Asia and China, and its artificial reproduction is complicated, with a relatively low success ratio in practice. In this study, the 42Sp50 gene was cloned from spotted scat. Tissue distribution analysis showed that 42Sp50 was mainly expressed in the ovary. qRT-PCR showed that 42Sp50 expression levels gradually decreased insignificantly in the ovaries from phase II to IV. Western blot analysis showed that 42Sp50 was highly expressed in the ovary, while it was almost undetectable in the testis. Immunohistochemistry analysis stained 42Sp50 mainly in the cytoplasm of the previtellogenic oocytes in ovaries of normal XX-female and sex-reversed XY-female. Aside from fish and amphibians, 42Sp50 was also identified in some reptile species using genomic database searching. Analyses of the transcriptome data from four different fish species (Hainan medaka (Oryzias curvinotus), silver sillago (Sillago sihama), Nile tilapia (Oreochromis niloticus), and Hong Kong catfish (Clarias fuscus)) revealed ovaries biased expression of 42Sp50 in all, similar to spotted scat. While the neighbor genes of 42Sp50 did not show ovary biased expression in the fish species analyzed. Bisulfite Sequencing PCR (BSP) results showed that the DNA methylation level of 42Sp50 promoter was low in ovaries, testes, and muscles. The luciferase reporter assay demonstrated that Dmrt4 activated 42Sp50 expression in the presence of Sf1 or Foxh1. These results suggest that 42Sp50 may be involved in regulating the early phase oocytes development of spotted scat.